2015
DOI: 10.1016/j.foodchem.2015.01.118
|View full text |Cite
|
Sign up to set email alerts
|

Fat and fatty acid composition of cooked meat from UK retail chickens labelled as from organic and non-organic production systems

Abstract: This study compared fat and fatty acids in cooked retail chicken meat from conventional and organic systems. Fat contents were 1.7, 5.2, 7.1 and 12.9 g/100 g cooked weight in skinless breast, breast with skin, skinless leg and leg with skin respectively, with organic meat containing less fat overall (P<0.01). Meat was rich in cis-monounsaturated fatty acids, although organic meat contained less than did conventional meat (1850 vs. 2538 mg/100 g; P<0.001). Organic meat was also lower (P<0.001) in 18:3 n-3 (115 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
7
10
0
Order By: Relevance
“…Table summarizes the 22 individual fatty acids measured in the samples from RC and three different processing stages. RC contains 22 kinds of fatty acids, which is greater than in broiler chickens, UK retail chickens, black‐bone silky chicken, Lingnan yellow chicken, and Chongren chicken . The main fatty acids were palmitic (C16:0), stearic (C18:0), oleic acid (C18:1n‐9), and linoleic (C18:2n‐6), which were similar to the findings of other studies.…”
Section: Resultssupporting
confidence: 86%
“…Table summarizes the 22 individual fatty acids measured in the samples from RC and three different processing stages. RC contains 22 kinds of fatty acids, which is greater than in broiler chickens, UK retail chickens, black‐bone silky chicken, Lingnan yellow chicken, and Chongren chicken . The main fatty acids were palmitic (C16:0), stearic (C18:0), oleic acid (C18:1n‐9), and linoleic (C18:2n‐6), which were similar to the findings of other studies.…”
Section: Resultssupporting
confidence: 86%
“…Meanwhile, lipid oxidation is an important factor in the flavor of dried cured meats, and it depends on a variety of factors, including the distribution of the fatty acids of raw meat, and the process and the storage conditions (Wang, Meng, Zhang, Zhou, & Zhang, ). The main precursors of meat flavor include water‐soluble components (free amino acids, small peptides, inorganic salts, and nucleic acid metabolites such as inosine, ribose) and lipid components (Dalziel, Kliem, & Givens, ; Khan, Jo, & Tariq, ). During the process of lipid oxidation, many carbonyl compounds are produced, which participate in Maillard reaction and form special flavor substances (Toldra & Flores, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Dalziel et al (2015) also reported that total fat content was higher in conventionally produced meat than organic ones. The higher content of protein in breast meat was caused by the use of free range to gain more moving in daily work in organic production, which is not common in conventional production.…”
Section: Discussionmentioning
confidence: 97%